Halal control point (HCP) analysis in the raw material supply chain using the failure mode effect and criticality analysis (FMECA) method - Sadeli, Akhmad; Rosyidi, Khafizh (Universitas Sultan Ageng Tirtayasa, 2025)
The growing demand for halal-certified food in institutional food services underscores the importance of structured risk management across the raw material supply chain. Despite regulatory requirements, many food service providers still face challenges in identifying and controlling halal-related risks, particularly in upstream processes. This study employed a cross-sectional design and applied the Failure Mode, Effects, and Criticality Analysis (FMECA) method to assess and prioritize halal risks across eight categories of raw materials. Data were collected from 30 respondents, including procurement staff, team leaders, and crew members, using structured questionnaires and interviews. Risk Priority Numbers (RPNs) were calculated based on severity, occurrence, and detection scores. The findings showed that meat and meat products had the highest RPN (94), indicating a tolerable but high-priority risk requiring strict control measures during procurement. Other categories, such as extra food, snacks, vegetables, fruits, spices, side dishes, and rice, were classified as acceptable risks but still require regular monitoring. These results highlight the effectiveness of the FMECA method in identifying critical Halal Control Points (HCPs) and supporting risk-based decision-making within halal assurance systems. Institutional food service providers are encouraged to adopt quantitative methods, such as FMECA, to enhance the effectiveness of halal risk mitigation strategies. Further studies with a broader scope and cross-industry comparisons are needed to strengthen halal integrity across diverse supply chain contexts.